Erratum to: B ¯ → D ¯ D $$ \overline{B}→ \overline{D}D $$ decays and the extraction of f d /f u at hadron colliders - Jonathan Davies; Martin Jung; Stefan Schacht (Journal of High Energy Physics)
A correction to this paper has been published: https://doi.org/10.1007/JHEP01(2024)191